An agent-based negotiation model for supplier selection of multiple products with synergy effect. Issue 1 (January 2015) - Yu, Chunxia; Wong, T.N.
Highlights The model supports supplier selection for multiple products with synergy effect. The negotiation scheme of the model was elaborated for multi-product environment. A MAS was developed to realize the proposed model. The buyer and suppliers can exploit the synergies between products by the model. Simulations are conducted to demonstrate the functions of the model.